Mengungkap Validitas Penafsiran Bi al-Ra’yi Tafsir al-Kasysyaf: Antara Retorika Bahasa dan Bias Teologi - Akhmad; Alif Akbar Hidayatullah (ejournal.nurulqadim.ac.id, 2025)
This paper discusses the figure of al-Zamakhshari, a renowned exegete from the Mu’tazilite school, widely known for his monumental work of exegesis, al-Kasysyaf. The work is widely recognized for its deep linguistic and rhetorical approach, with a strong emphasis on the Balaghah (rhetoric) aspects of the Qur'an. The aim of this paper is to assess the validity of the Bi al-Ra’yi method in al-Kasysyaf, examining the interpretive methods used by al-Zamakhshari and the influence of Mu’tazilite theological thought on his interpretations. Using a qualitative and library research approach, this study finds that while al-Kasysyaf is highly regarded for its linguistic and literary qualities, readers should be cautious of the theological bias it contains. The paper concludes with a reflection on the contributions and controversies of al-Kasysyaf in the tradition of Islamic scholarship.